Performance appraisal and management: The developing research agenda - Fletcher, Clive (Journal of occupational and organizational psychology, 2001)
Performance appraisal has widened as a concept and as a set of practices and in the form of performance management has become part of a more strategic approach to integrating HR activities and business policies. As a result of this, the research on the subject has moved beyond the limited confines of measurement issues and accuracy of performance ratings and has begun to focus more of social and motivational aspects of appraisal. This article identifies and discusses a number of themes and trends that together make up the developing research agenda for this field. It breaks these down in terms of the nature of appraisal and the context in which it operates. The former is considered in terms of contemporary thinking on the content of appraisal (contextual performance, goal orientation and self awareness) and the process of appraisal (appraiser‐appraisee interaction, and multi‐source feedback). The discussion of the context of appraisal concentrates on cultural differences and the impact of new technology. In reviewing these emerging areas of research, the article seeks to explore some of the implications for appraisal practice at both organizational and individual levels.